Public R&D Investment in Economic Crises - Maikel Pellens; Bettina Peters; Martin Hud; Christian Rammer; Georg Licht (ZBW - Leibniz Information Centre for Economics, 2021)
We study the cyclicality of public R&D in 28 OECD countries (1995 - 2017). While procyclical on average, public R&D reacts asymmetrically over different phases of the business cycle and becomes acyclical during recessions. It is also heterogeneous across countries: Innovation leaders and followers behave countercyclically during recessions while moderate innovators behave procyclically. Furthermore, the share of public R&D allocated to the business sector is countercyclical, but the thematic composition remains stable. These results, not driven by countries' financial constraints, imply that countries behind the innovation frontier might strengthen their resilience to economic crises by adopting countercyclical R&D strategies.
Keywords: O38; H50; H12; E32; 330; R&D; Public Policy; Business Cycle